2022
DOI: 10.3390/toxics10020080
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Novel Solvent for Optimum Extraction of Anionic Surfactants in Water

Abstract: Anionic surfactants (AS) are detrimental aquatic pollutants due to their well-characterized toxicity to aquatic organisms. The concentration of AS in aquatic environments is increasing because of their extensive use in many industries and households. The standard reference method for AS analysis is to determine a methylene blue active substance (MBAS) complex formed between AS and the methylene blue (MB) cation by using chloroform. However, chloroform has a low AS extraction efficiency and other limiting prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Elimination of anionic interferences by the washing process is the prerequisite step for analysis of AS in aquatic samples [10][11][12][13][14]16]. Any washing procedure should remove the methylene blue-anion (MB + A − ) complex present in an aqueous or solvent phase.…”
Section: Removal Of Anionic Interferencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Elimination of anionic interferences by the washing process is the prerequisite step for analysis of AS in aquatic samples [10][11][12][13][14]16]. Any washing procedure should remove the methylene blue-anion (MB + A − ) complex present in an aqueous or solvent phase.…”
Section: Removal Of Anionic Interferencesmentioning
confidence: 99%
“…Ideal criteria for the solvent to be used in the analysis of AS in different types of water are that it should have a high extractability, a short phase separation time, a low volatility, a low solubility in water, a lower density than water, and a lower potential health hazard [14][15][16]. However, chloroform has a low AS extraction efficiency and a relatively high density and volatility [10,[14][15][16][17][18][19]. Yoon et al [16] reported that no single solvent in SDS extraction could, among several solvents screened, meet such ideal criteria.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations